Função social do tributo: reflexões sobre a Teoria Geral do Direito Tributário - Stecca, Gabriel Capristo (2018)
The present research seeks to develop the concept and the application of the social function of tax. The tax law is thought under aspects of the General Theory of Law. There is an intense discussion between law and politics and on the inception and clashes between legal positivism, justarilism and post-positisvism. The dissertation progresses and is accredited in the Robert Alexy‘s Theory of Principles; reanalyses tax law institutes already consolidated in the Republican Constitution of 1988, such equality, private property, solidarity, dignity and makes a heterodox theoretical about the Marxist view of tax law. All research is based on the idea of tax justice, the accomplishment of the social function of tax as a means of financing the State, promote the social equality and reduce the socioeconomics distances